Penguatan Literasi Penulisan Artikel Berbasis SEO bagi Lembaga Pendidikan Berkebutuhan Khusus - Emilya Setyaningtyas; Anita Yunia; Wulan Yulianti; Aprida Mardelina Sihombing; Della Melianie Hery (Dharma: Jurnal Pengabdian Masyarakat, 2026)
Rumah Autis, a social institution under the Yayasan Cahaya Keluarga Fitrah (CAGAR Foundation), was established in 2024 and operates seven branches across Greater Jakarta (Jabodetabek) and Karawang. The institution provides affordable and free therapy and educational services for individuals with autism and Children with Special Needs, especially for underprivileged families.However, Rumah Autis faces challenges in managing its digital presence, including limited writing skills, lack of SEO knowledge, outdated and unstructured content, and inconsistent production of high-quality articles.To address these issues, a training and mentoring program in article writing and website SEO optimization was implemented. The program aims to improve content quality, increase visibility of autism-related information, strengthen community engagement, and enhance the sustainability of the website through better use of digital technology. As a result of the program, website optimization improved outreach, and 81.25% of the 16 participants demonstrated increased knowledge, supporting Rumah Autis in expanding its impact for children with special needs in Indonesia.